Gambaran Pengetahuan dan Sikap Remaja Kelas VIII Tentang Lesbian, Gay, Biseksual, Transgender (LGBT) di SMP Negeri 24 Padang - Riska Pitriyani; IIs Niawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
According to the Indonesian Ministry of Health's report on HIV cases for the period January – March 2017, the total number of HIV virus infections reported was 10,376 people. The highest percentage of HIV factors in risky sex was among men who have sex with men (MSM) (28%), heterosexuals (24%), injecting needles (2%) and others (9%). In the West Sumatra region, in 2022, in 4 points, namely Padang City, Bukitinggi, Solok and Solok Regency, it is estimated that there will be 14,469 people who have sex with men (MSM) or gay people in West Sumatra (Ministry of Health of the Republic of Indonesia, 2022). The aim of this research is to determine the description of the knowledge and attitudes of class VIII teenagers regarding LGBT at SMP Negeri 24 Padang in 2024.This type of research is